Morphological, pathological and phylogenetic analyses of Phytophthora heterospora causing durian stem canker disease in the eastern coast of Peninsular Malaysia - Johari, Muhammad Iqbal Hakim; Zulperi, Dzarifah; Saad, Norsazilawati; Ismail, Siti Izera; Hakiman, Mansor; Karam, Daljit Singh; Kusuma, Ramadhani Mahendra (John Wiley and Sons, 2025)
Durian (Durio zibethinus), a highly popular tropical fruit in Southeast Asia, faces a major challenge from stem canker disease, primarily caused by oomycetes. This study aimed to identify and characterise the causal agent of durian stem canker on the eastern coast of Peninsular Malaysia. A combination of morphological, pathological and phylogenetic analyses was employed to comprehensively understand the pathogen's characteristics. A series of samplings was conducted on several durian orchards. Isolates were identified using morphological characteristics, DNA sequences and phylogenetic analysis of multiple markers, namely the internal transcribed spacer (ITS) region of the ribosomal RNA gene cluster, β‐tubulin (BTUB) and cytochrome c oxidase subunit I (COXI). Three representative isolates were selected for pathogenicity tests on durian seedlings. The sampling sites had disease incidence ranging from 10% to 54%. A total of 25 isolates were recovered from symptomatic tissues and showed morphological features that resembled those of Phytophthora species. Phylogenetic analyses using concatenated markers put all of the isolates in the same group as Phytophthora heterospora, supported with 98% maximum‐likelihood bootstrap values. The result of the pathogenicity tests revealed P. heterospora as the causal agent of stem canker of durian.